Study on chemical constituents and bioactivities of the fruits of Dipterocarpus retusus of Viet Nam - Hung, Ho Dac; Tien, Doan Huy; Ngoan, Nguyen Thi; Duong, Ba Thi; Viet, Do Quoc; Dien, Pham Gia; Anh, Bui Kim (Vietnam Journal of Science and Technology, 2019)
The first study on chemical constituents and biological activities of fruits of Dipterocarpus retusus Blume (Dipterocarpaceae.) growing in Vietnam was reported. Column chromatography of the ethyl acetate extract led to the isolation of five compounds: eleutherol (1), 3, 5, 4' - trihydroxy - trans - stilbene (2), polydatin (3) and β-sitosterol (4), β-sitosterol-3-O-β-D-glucopyranoside (5). Their structures were elucidated based on the NMR spectroscopic methods and comparison with literature date. The extracts from fruits of D. retusus Blume by n-hexane, ethyl acetate and butanol, consecutively, were evaluated for antioxidative and cytotoxic activities.